Factors Affecting the Individual Stock Price Index (IHSI) Industrial Manufacturing Sector in Indonesia, Automotive Sub Sectors, and Components in Indonesia Stock Exchange (IDX) - Salim, M Noor; Sutarjo (The Economics and Finance Letters, 2020)
This study aims to examine and analyze: (1) the Effect of Current Ratio (CR), Debt of Equity Ratio (DER), Return On Assets (ROA) and Return On Equity (ROE) on the Individual Stock Price Index (IHSI), ( 2) Effect of Current Ratio (CR), Debt of Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE) and Individual Stock Price Index (IHSI) on Investment (INV), (3) Effect of Price Index Individual Share (IHSI) to Investment (INV). The population of this study is the Manufacturing Industry company in the Automotive and Components Industry sub-sector in Indonesia with an observation period from 2014 to 2018, consisting of a sample of 10 Automotive Industry companies and components. Data analysis techniques in this study used Panel Data Regression analysis, the regression model used was to combine cross-data data with time-series data. The results of data analysis prove that the variable Current Ratio (CR), Debt of Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE) Simultaneous significant positive effect on the Individual Stock Price Index (IHSI), but together with or simultaneously Variable Current Ratio (CR), Debt of Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE) and The Individual Share Price Index (IHSI) has a positive effect significant to Investment (INV), the Individual Stock Price Index (IHSI) variable has no significant impact on Investment (INV) either partially or simultaneously.